Quantitative Proteomics Revealed the Pharmacodynamic Network of Bugu Shengsui Decoction Promoting Osteoblast Proliferation - Wei, Xu; Qi, Baoyu; Ma, Ruyun; Zhang, Yili; Liu, Ning; Fang, Shengjie; Zhu, Yanning; Xie, Yanming; Dai, Jianye; Zhu, Liguo (Frontiers in Endocrinology, 2022)
Background and Objective: With high morbidity and disability, osteoporosis is a worldwide bone metabolism disease, regulated by complex pathological processes. Insufficient osteogenesis is greatly essential to osteoporosis. Traditional Chinese Medicine, a complex natural herbal medicine system, has increasingly attracted attention all over the world. Bugu Shengsui Decoction, a compound formula for osteoporosis, has significant clinical effects in the treatment of osteoporosis. Yet the detailed mechanisms are unclear. Thus, we investigated the effects and mechanism of Bugu Shengsui Decoction on osteoporotic rats and osteoblasts in vitro. Methods: In this study, we evaluated the effect of Bugu Shengsui Decoction in an animal model of orchiectomy. Multi-pharmacology indexes revealed that Bugu Shengsui Decoction obviously improved bone metabolism, bone mineral density, bone morphology, and biomechanics in the castrated rats. Then, serum pharmacology was employed to unveil that Bugu Shengsui Decoction promoted the proliferation and differentiation of osteoblasts. Moreover, quantitative proteomics combined with RNA interferes assay was used to analyze and verify the pathway and key targets in pro-proliferation of MC3T3-E1 cells. Results: Bugu Shengsui Decoction obviously improved the worse parameters of bone metabolism, bone mineral density, bone morphology and biomechanics in castrated rat model. In vitro, Bugu Shengsui Decoction exerted proliferation and differentiation promoting effects of osteoblasts induced by serum-starved. Moreover, quantitative proteomics analysis combined with RNA interfere assay illustrated that Bugu Shengsui Decoction promoted osteogenesis via PI3K-AKT pathway. Conclusion: Summarily, our discoveries certify that Bugu Shengsui Decoction is an effective treatment for osteoporosis via PI3K-AKT. This study is not only a beneficial attempt to explore the detailed mechanism of Traditional Chinese formula, but also will provide inspiration for the treatment strategy of osteoporosis.